3D printing of a continuous fiber-reinforced composite based on a coaxial Kevlar/PLA filament. (16th March 2021) - Cersoli, Trenton; Yelamanchi, Bharat; MacDonald, Eric; Carrillo, Jose Gonzalo; Cortes, Pedro
Additive manufacturing has allowed for the production of complex and mass customized geometries, but often at the expense of mechanical performance, a penalty which can be in part mitigated with the fabrication of composite parts. Thermoplastic structures fabricated with material extrusion additive manufacturing stand to be improved in terms of fracture toughness with the integration of continuous fibers. The present research program has investigated the production of a continuously reinforced filament to be used in open-source fused filament fabrication systems. Three different volume fractions of Kevlar fibers were incorporated into a polylactic acid (PLA) thermoplastic filament. It was observed that a 20% fiber volume fraction resulted in a doubling of the tensile strength relative to the unreinforced PLA parts. High-velocity impact tests were also performed on the reinforced printed thermoplastic material, and it was observed that the composite with the highest fiber volume fraction provided an impact energy resistance improved by a factor of four, relative to the plain PLA. The reinforced fibers have shown to restrain the penetration of the projectile at velocities similar to those that perforated the unreinforced PLA. The present work has demonstrated the production of printed composites without the need of modifying the extruding systems of a commercial 3D printer. This approach could represent an alternate and feasible process for producing continuously reinforced 3D-printed thermoplastic parts with utility for high-velocity impact applications.